2013
DOI: 10.1007/s12160-013-9540-4
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Racism: The Impact of Prayer on Cardiovascular Reactivity and Post-stress Recovery in African American Women

Abstract: Coping with racism by utilizing prayer may have cardiovascular benefits for African American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
3
37
2
Order By: Relevance
“…In addition, although our sample size was consistent with previous studies in this area (e.g., Neblett & Roberts, 2013; Utsey & Hook, 2007), our sample composition was relatively homogenous with respect to age and apparent health status. Although these characteristics pose a potential challenge to the generalizability of our findings, it is notable that similar effects were observed in studies of adults with greater variability in age and health status (i.e., Cooper et al, 2014; Dorr et al, 2007; Wagner et al, 2015). In addition, focusing on the impact of racial discrimination among emerging adults has become increasingly important as research suggests that discrimination may begin taking a serious biological toll on African Americans before or by emerging adulthood (Brody et al, 2014; Williams & Mohammed, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…In addition, although our sample size was consistent with previous studies in this area (e.g., Neblett & Roberts, 2013; Utsey & Hook, 2007), our sample composition was relatively homogenous with respect to age and apparent health status. Although these characteristics pose a potential challenge to the generalizability of our findings, it is notable that similar effects were observed in studies of adults with greater variability in age and health status (i.e., Cooper et al, 2014; Dorr et al, 2007; Wagner et al, 2015). In addition, focusing on the impact of racial discrimination among emerging adults has become increasingly important as research suggests that discrimination may begin taking a serious biological toll on African Americans before or by emerging adulthood (Brody et al, 2014; Williams & Mohammed, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…This effect was evident for African-Americans but not for Whites. Most recently, in a small laboratory study of 81 African-American women, Cooper and colleagues (Cooper et al 2014) found that women who reported using prayer as a coping strategy for racist events were buffered against the negative effects of a racism-related anger recall task on negative affect and cardiovascular reactivity (Cooper et al 2014). These findings provide some preliminary support for the notion that religious involvement and religious behaviors may attenuate the effects of discrimination on outcomes, particularly for African-Americans.…”
Section: Emerging Areas Of Interestmentioning
confidence: 99%
“…Table 9 Angry Rumination Reactivity and Recovery Moderator Analyses Note. *p< .05; **p< .01; ***p< .001 Meta-regression revealed that biological sex and race/ethnicity did not explain a significant amount of variability in effect sizes to angry rumination for reactivity: Benight et al (1997) 1.290 0.510 Brown (1999) 1.300 0.170 Brummett et al (2009) 1.030 0.080 Burns (2006) 0.940 0.170 Burns et al (2003) 0.410 0.310 Carels et al (1998) 1.500 0.230 Cohen (2010) 0.810 0.150 Cooper et al (2014) 1.690 0.180 Ditto, Miller, & Marice (1987) Foster et al (1999) 1.930 0.490 Foster et al (1997) 0.160 0.350 Fredrickson et al (2000) 0.170 0.170 Friedberg et al (2007) 0.720 0.150 Gerin et al (2006) 1.280 0.200 Glynn et al (2002) -0.690 0.340 Henninger (2001) 1.200 0.150 Ironson et al (1992) 0.920 0.490 Jonassaint et al (2009) 0.410 1.420 Kario et al (2002) 1.310 1.420 Lawler et al (1995) 0.880 0.140 Leon et al (2007) 1.820 0.220 Linegerger, M.D. (2005) 0.130 0.200 McLain (2010) 0.720 0.160 McClelland et al (2008) 0.010 0.150 Neumann & Waldstein (2001) 1.000 0.230 Neumann et al (2004) 1.270 0.170 Ratnasingam & Bishop (2007) 1.350 0.170 Richman et al (2007) 0.900 0.120 Ruiz (2003) 1.360 0.140 Rutledge et al (2001) 0.760 0.130 Sinha et al (1992) 1.370 0.300 Smeijers et al (2014) 1.860 0.390 Suarez et al ( 2004) 1.440 0.120 Synowski (2008) 1.590 0.330 Vaughn (2008) 0.310 0.170 Vrana et al (2009) 0.400 0.130 …”
Section: Angry Ruminationmentioning
confidence: 99%
“…(2005) 0.130 0.200 McLain (2010) 0.720 0.160 McClelland et al (2008) 0.010 0.150 Neumann & Waldstein (2001) 1.000 0.230 Neumann et al (2004) 1.270 0.170 Ratnasingam & Bishop (2007) 1.350 0.170 Richman et al (2007) 0.900 0.120 Ruiz (2003) 1.360 0.140 Rutledge et al (2001) 0.760 0.130 Sinha et al (1992) 1.370 0.300 Smeijers et al (2014) 1.860 0.390 Suarez et al ( 2004) 1.440 0.120 Synowski (2008) 1.590 0.330 Vaughn (2008) 0.310 0.170 Vrana et al (2009) 0.400 0.130 Waldstein et al (2002) 1.360 0.160 Waldstein et al (2000) 0.830 0. (2007) 1.700 0.540 Brown (1999) 1.600 0.180 Ayduk & Kross (2008) 0.080 0.150 Brummett et al (2009) 1.220 0.090 Burns (2006) 1.300 0.180 Burns et al (2003) 1.550 0.350 Carels et al (1998) 2.040 0.250 Cohen (2010) 1.310 0.160 Cooper et al (2014) 2.080 0.190 Ditto et al (1987) a 0.370 0.320 Ditto et al (1987) b 0.700 0.310 Fredrickson et al (2000) 0.680 0.180 Friedberg et al (2007) 1.420 0.160 Gerin et al (2006) 1.840 0.220 Glynn et al (2002) 0.780 0.350 Henninger (2001) 1.500 0.150 Ironson et al (1992) 1.380 0.520 Jonassaint et al (2009) 1.700 0.160 Lawler et al (1995) 1.480 0.150 Leon et al (2007) 2.040 0.230 Linegerger (2005) 0.210 0.200 McLain (2010) 1.810 0.190 Neumann et...…”
Section: Angry Ruminationmentioning
confidence: 99%
See 1 more Smart Citation